Promoting readiness and engagement in pain rehabilitation for youth and families: Developing a pediatric telehealth motivational interviewing protocol - Allison M. Smith; Deirdre E. Logan (Wiley, 2022)
Abstract Objective Intensive interdisciplinary pain treatment (IIPT) is a promising approach for youth with complex, disabling, refractory pain conditions. However, youth and families who initiate IIPT without sufficient acceptance of its focus on functional rehabilitation or readiness to adopt a self‐management approach to their pain may face challenges in IIPT and/or experience suboptimal outcomes. Motivational interviewing (MI) techniques have been shown to enhance readiness to make a number of health behavior changes for adults and youth, but it has not been systematically examined in the context of pediatric IIPT. The authors developed an MI telehealth intervention protocol explicitly designed to prepare youth and families for admission to IIPT. Method The protocol development process is detailed here, including influential models, expert consultation, and feedback from IIPT clinical experts. The intervention protocol was then piloted with a group of eligible families to elicit feedback and prompt further refining. Feasibility and acceptability were explored through measures of treatment engagement and satisfaction. Results The Promoting Readiness and Engagement in Pain Rehabilitation (PREPaRe) intervention protocol contains four modules aimed to enhance youth and parent readiness to adopt a self‐management approach to persistent pain, through a motivational interviewing approach. Initial responses from the test group suggested high levels of treatment engagement and treatment satisfaction with PREPaRe. Conclusions PREPaRe appears feasible to administer and acceptable to families of youth with persistent pain seeking IIPT. Implications for implementation are discussed. Further study via randomized control trial is warranted. Trial registration ClinicalTrials.gov identifier: NCT04093921.